Assessing the current state of teaching to develop competency in understanding the living world based on nature reserves in high school biology education in Vietnam - Thuy, Dung Nguyen; Hung, Son Nguyen Lan; Thanh, Hoi Phan Thi (Kasetsart Journal of Social Sciences, 2026)
In the context of Vietnam’s 2018 General Education Curriculum reform, teaching is oriented toward the development of students’ competencies and integrating practical experience. Nature reserves, which are biodiversity-rich protected areas, provide an ideal learning environment to directly observe and illustrate abstract scientific theories. Nature reserve-based teaching stimulates curiosity, fosters critical thinking and environmental consciousness, and promotes mental well-being among students, aligned with the competency in understanding the living world - one of the three core components of competencies in Biology (biological cognition, understanding the living world, and applying knowledge and skills in life). This study surveyed 824 Biology teachers from high schools across various provinces in Vietnam, utilizing a Likert-scale questionnaire and open-ended questions. The findings indicate that most teachers preferred using materials such as images, videos, and questions related to nature reserves in their classrooms to develop students’ competency in understanding the living world. However, the results also show that methods were less frequently adopted as they often require more time, resources, and financial support, such as experiential learning, practical activities, or project-based learning. Differences in using these methods were observed between teachers in rural and urban schools. Furthermore, the primary challenges stem from financial constraints, limited involvement from school students and communities, and a lack of nature-based teaching expertise that can be solved by funding environmentally responsible businesses, support from nature reserve staff, and integrating a formal curriculum.